IMPLIKASI PP 46 TAHUN 2013 ATAS PPh BADAN, LABA BERSIH USAHA SETELAH PAJAK, DAN PEREDARAN BRUTO - Hakim, Firdaus Miftahul; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the calculation of corporate income tax and net profit after corporatetax when it is calculated based on the Law No. 36 of 2008 and the Goverment Regulation No. 46 of 2013 and tofind out whether the implementation of Goverment Regulation No. 46 of 2013 obstructs the enhancement of theamount of gross income of the company or not. The object of the research is PT. Duta Warna Creation which hasgross income less than Rp4,800,000,000,- (Four Billion Eight Hundred Million Rupiahs). This research isdescriptive qualitative research. The results of this research are when the calculation of corporate income taxwhich is based on Goverment Regulation No. 46 of 2013 is used; when the amount of the corporate income taxexpense of PT Duta Warna Creation is higher than the calculation which is based on the Law No. 36 of 2008, sothe net profit venture after tax based on the calculation of Goverment Regulation No. 46 of 2013 will be smallerthan the calculation that is based on the Law No. 36 of 2008. And the amount of the increasing gross incomeevery years has increased so the implementation of these rules do not become the obstacle to the enhancement ofthe gross income of PT. Duta Warna Creation.Keywords: Goverment regulation no. 46 of 2013, corporate income tax, law no. 36 of 2008